“Kemanakah Hutan Kami ?” Dinamika Sosial dan Kontestasi Antara Pihak-pihak yang Terlibat dalam Pengelolaan Hutan di Kabupaten Seruyan Kalimantan Tengah - Rusmin Octovianus (Universitas Khairun, 2015)
Social dynamics in forest management is quite complicated. Thelocals are the hereditary lived in adjacent of forest area and use it forsupporting their daily need. The timber and mining company exploited offorest for earning of profit. The government stands in the crossroad, theymust manage the forest for conservation area while at the other hand theymust increase the regional income.The euphoria of reformation has encouraged the RegionalAutonomies (decentralization) and has rolled over of new policies by theregional government in term of the natural resources management. Despitethe regional government is now concerning the locals who their needs aredepend on the forest but the conflict lie where the people with differentinterest meet. In this case, it talks about forest exploitation, the locals are themisfortune one.The article shall describe the social dynamic and the contestedamong parties related to the forest management in Seruyan DistrictProvince of Central Kalimantan.